Myocardial Viability: Evolving Insights and Challenges in Revascularization and Functional Recovery - Kristoffer Ken Ralota; Jamie Layland; Kyi Thar Han Win; Nay M. Htun (Journal of Cardiovascular Development and Disease)
The prevalence of heart failure, driven significantly by ischemic heart disease, continues to rise globally. Myocardial viability—the potential ability of dysfunctional myocardium to recover contractile function after revascularization—remains an ongoing key area of research in managing ischemic cardiomyopathy. Advances in imaging modalities, including PET/SPECT, cardiac MRI, and dobutamine stress echocardiography, have enabled identification of viable myocardium that can potentially predict their functional recovery following revascularization. Despite these advances, recent evidence from major trials questions the routine reliance on viability testing for revascularization guidance. These studies found a limited correlation between myocardial viability and improved outcomes in key metrics including mortality. Furthermore, they highlighted the effectiveness of guideline-directed medical therapy in improving left ventricular function independent of revascularization. This narrative review explores the concept of myocardial viability, its assessment through contemporary imaging techniques, its clinical utility in decision making for revascularization, and future directions.